Growth chaflacteristics of human keratinocytfs in vitro and its compailison using human amnion membrane andfibrin glue as a scaffold - Ananda, Aravazhi (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2009)
The amniotic membrane is a natural biological scaffold that is widely used to promote and speed wound healing. An ideal scaffold should be bio-compatible and be able to support and maintain the activity of cells involved in wound healing. Furthermore, it should allow angiogenesis in order to support the viability and activity of cells, in addition to the anchorage and migration ofkeratinocytes to achieve wound closure. In this study, normal human epidermal keratinocytes were seeded on an amniotic membrane or the fibrin glue TISSEEL (Baxter). The proliferation and growth of viable keratinocytes was documented over three days. The percentage of viable keratinocytes proliferating on the amniotic membrane scaffold was 23.33%, 26.15% and 31.82% after 24, 48 and 72 hours, respectively. The percentag;e of viable keratinocytes proliferating on the fibrin scaffold was 72.36%, 75.05% and 78.82% after 24, 48 and 72 hours, respectively. The percentage of viable keratinocytes was significantly higher on the fibrin scaffold (p < 0.005). Immune rejection due to the cellular components of the amniotic membrane prevents the proliferation of keratinocytes in vitro. The human amniotic membrane needs to be de-epithelialized in order to support the growth of various cell lines. Fibrin glue, however, supports the growth ofkeratinocytes in vitro and has the potential to become an ideal scaffold for a skin substitute.